Penggunaan Media Online Pada Pembelajaran Daring untuk Sekolah Dasar/ Madrasah Ibtidaiyah - Trisa Febriyanti (EduBase : Journal of Basic Education, 2022)
This article is an article that discusses the use of online media in online learning, especially for elementary/MI students and the effectiveness of the learning process. The method that will be used in this article is the collection of material and theoretical studies or literature reviews taken and obtained from books and journals. The results show that the online learning done by SD/MI students is less effective and reduces the interest of SD/MI students in the learning process, especially when working on assignments given by their teachers. The purpose of the research applied in this study is to find out how the effectiveness of funds in the teaching and learning process in school institutions is smooth, which is based on online media and through an intermediary. This is referred to as online learning which is used in the learning process by teachers or lecturers to students or students in every educational institution in Indonesia. The data collection method used in this article uses data collection techniques and information studies regarding the use of online media in online learning for SD/MI in general. The results of the research obtained are that online education makes students more independent in exploring the material provided by teachers and lecturers, apart from that online learning is successful in minimizing crowds and manifesting social distancing. However, it is still lacking in the implementation process and results in inefficiency and other obstacles in the form of unequal economic abilities of each student. Limited internet quota usage and insufficient network. Where educators are needed in managing learning starting from planning, organizing, mobilizing and evaluating in order to increase the effectiveness of the teaching and learning process during the current COVID-19 pandemic, especially the implementation of distance learning in the school environment. Therefore, educators must be able to deal with this In addition to the different implementation processes, the delivery of materials and curriculum at schools was also affected by the outbreak. (Supiana Akhmad Arianto, 2020) Various applications that are expected to support the teaching and learning process are also used optimally, for example the Google Classroom application, Google Meet, Zoom and many more. Although the use of applications can facilitate the teaching and learning process during the current pandemic, the various obstacles experienced by students are increasingly diverse. Both in terms of financial and in terms of network. In addition, the effectiveness of this learning process is still in doubt for some people, especially for elementary/MI students Abstrak Artikel ini merupakan artikel yang membahas penggunaan media online pada pembelajaran daring utamanya bagi siswa/siswi SD/MI dan keefektifan proses pembelajaran tersebut. Adapun metode yang akan digunakan pada artikel ini adalah pengumpulan materi dan kajian teori atau kajian pustaka yang diambil dan didapatkan pada buku dan jural. Hasil menunjukkan pembelajaran yang lakukan secara daring oleh siswa/siswi SD/MI kurang efektif dan menurunkan minat siswa/siswi SD/MI pada proses pembelajaran terutama pada saat pengerjaan tugas yang diberikan oleh guru mereka.Tujuan penelitian yang di terapkan pada penelitian kali ini yaitu mengetahui bagaimana kelancaran dana efetifitas dalam proses belajar mengajar di lembaga lembaga sekolah, dimana pada dasarkan di haruskan menggunakan media onlie dan melalui sebuah perantara. Hal ini di sebut sebagai pembelajaran onine yang di gunakan dalm proses pembelajran oleh guru ataupun dosen kepada siswa atau mahasiswa di setiap lembaga pendidikan di Indonesia.Adapun metode pengumpulan data yang dilakukan pada artikel ini menggunakan teknik pengumpulan data dan studi informasi mengenai penggunaan media online pada pembeajaran daring untuk SD/MI secara umum. Hasil riset yang di dapatkan ialah pendidikan daring yang dilakukan membuat pelajar lebih mandiri dalam mendalami sebuah materi yang di berikan oleh guru maupun dosen terlepas dari itu online learning berhasil untuk meminimalisir adanya kerumunan dan memanifestasikan social distancing. Akan tetapi masih kurang dalam proses penerapannya dan mengakibatkan ketidakefesienan dan hambatan lain berupa, tidak samanya kemampuan ekonomi setiap peserta didik. Keterbatasan penggunaan kuota internet serta jaringan yang belum mencukupi. Dimana pera pendidik di perlukan dalam mengelola pembelajran mulai dari perencanaan, pengorganisasian, peggerakan dan evaluasi guna meningkatkan efektifitas proses belajar mengajar di masa pandemic COVID-19 saat ini, terutama pelaksanaan pembelajaran jarak jauh di lingkungan sekolah. Oleh karena itu pendidik harus mampu menghadapi hal ini. Selain proses pelaksanaannya yang berbeda, penyampaian materi dan juga kurikulum pada sekolah pun tidak luput dari pengaruh wabah tersebut. (Supiana Akhmad Arianto ,2020)Berbagai aplikasi yang diperkirakan menunjang proses belajar-mengajar juga dipergunakan secara maksimal contohnya aplikasi google classroom, google meet, zoom dan masih banyak lagi. Meskipun penggunaan aplikasi dapat mempermudah proses belajar-mengajar dimasa pandemic saat ini, berbagai kendala yang dialami oleh pelajar pun semakin beragam. Baik dari segi finansial maupun dari segi jaringan. Selain itu, keefektifan proses pembelajaran ini juga masih diragukan bagi sebagian orang utamanya untuk siswa dan siswi SD/MI.